2013
DOI: 10.2522/ptj.20120156
|View full text |Cite
|
Sign up to set email alerts
|

Work Reintegration for Veterans With Mental Disorders: A Systematic Literature Review to Inform Research

Abstract: Comprehensive literature review found limited knowledge about how to integrate people with mental disorders into a new workplace after a prolonged absence (>1 year). Even more limited knowledge was found for veterans. The results informed the next steps for our research team to enhance successful reintegration of veterans with mental disorders into the civilian workplace.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Individuals with severe mental illnesses including bipolar and major depressive disorders, and schizophrenia as well as military veterans with post-traumatic stress disorder (PTSD) experience disabling symptoms that hinder their vocational outcomes (1, 2). Although approximately 60% of individuals receiving mental health services want to work and may actively seek employment (3, 4), they have low employment rates.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with severe mental illnesses including bipolar and major depressive disorders, and schizophrenia as well as military veterans with post-traumatic stress disorder (PTSD) experience disabling symptoms that hinder their vocational outcomes (1, 2). Although approximately 60% of individuals receiving mental health services want to work and may actively seek employment (3, 4), they have low employment rates.…”
Section: Introductionmentioning
confidence: 99%
“…Job re-entry is particularly challenging for Veterans with psychiatric diagnoses (VanTil et al, 2012), particularly for those who also have substance use problems (Burnett-Zeigler et al, 2012). In response to difficulties finding or holding a job, a Veteran with a psychiatric condition may apply for service-connection disability.…”
Section: Introductionmentioning
confidence: 99%
“…Americans have gone to and returned from war with a multitude of physical and psychological traumas and readjustment challenges, a recent review of the work reintegration literature concluded that there is "limited knowledge about how to reintegrate people with mental disorders" (Van Til, Fikretoglu, Pranger, Patten, Wang, Wong et al, 2013). Thus, the role of the civilian work domain in shaping posttraumatic stress symptoms ("PTSS") is an underexplored area ripe for investigation by social scientists and occupational health practitioners motivated to improve the long neglected health, economic stability, and lifelong well-being of veterans entering, reentering, or returning to work, their families, and society.…”
Section: List Of Tablesmentioning
confidence: 99%
“…Other substantive questions related to the potential impacts of larger organizational influences within America's district forms of military cultures (e.g., air, sea, and land) and varying forms of civilian work organization (i.e., public, private, public-private) or civilian occupations (e.g., blue vs. white collar) were not investigated. As no unified theory of military-to-civilian work reintegration presently exists (e.g., Schultz, Chlebak, & Stewart, 2016;Van Til et al, 2013) this thesis study applied an integrated theoretical approach. Prior industrial, organizational, clinical and biopsychosocial theories, as well as scholarly military and occupational health perspectives and findings on "stressorstrain relationships" among military veterans and civilian workers in high-risk occupations informed conceptual distinctions and predicted associations among focal variables of interest.…”
Section: List Of Tablesmentioning
confidence: 99%
See 1 more Smart Citation